1999
DOI: 10.1097/00004424-199901000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Hamate Bone Fractures in Conventional X-Rays and High-Resolution Computed Tomography

Abstract: Fractures of the body and hook of the hamate cannot always be detected with certainty in the conventional X-ray image, even if different projectional planes are used. The HR-CT is the imaging procedure of choice for further clarification, and an axial or sagittal plane should be selected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 17 publications
2
38
0
2
Order By: Relevance
“…However, there were no complications in these patients related to the delayed diagnosis of distal bones fractures. Besides, the reported sensitivity of conventional X-rays for the detection of wrist fracture was 72.2% [29]. Some retrospective studies also suggested that 10-33% of patients with a proven distal bone fracture had no fracture visible on the conventional X-rays [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no complications in these patients related to the delayed diagnosis of distal bones fractures. Besides, the reported sensitivity of conventional X-rays for the detection of wrist fracture was 72.2% [29]. Some retrospective studies also suggested that 10-33% of patients with a proven distal bone fracture had no fracture visible on the conventional X-rays [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, oblique radiographs with the hand pronated 30° were routinely used for diagnosis. Although Andresen et al [13] and Kaneko et al [14] demonstrated that threedimension computed tomography (CT) findings proved to be superior to other radiographic imaging, CT imaging is not routinely used in our clinic due to the high cost and radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…CT was most accurate at detecting the fracture line and hook position [5,24,25], and it allowed us to determine the exact size of the fragment. Due to the distal thread length of the mini-screw used in this study, our technique is limited to a fragment size and radioulnar diameter of the hook of more than 5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated fractures of the hamate hook appear to occur more frequently than previously reported, which could be attributed to the increasing popularity of sports activities, such as golf, tennis, baseball, and hockey, more careful assessment of wrist injuries, and improved radiographic imaging [1][2][3][4][5]. Hook fractures are caused by direct or indirect trauma or a combination of both.…”
Section: Introductionmentioning
confidence: 99%